2013
DOI: 10.1590/s0004-28032013000200022
|View full text |Cite
|
Sign up to set email alerts
|

ASSESSMENT OF THE RESPONSE OF PATIENTS WITH CROHN'S DISEASE TO BIOLOGICAL THERAPY USING NEW NON-INVASIVE MARKERS: lactoferrin and calprotectin

Abstract: Calprotectin and lactoferrin are not useful for monitoring inflammatory activity in Crohn's disease patients who are subjected to biological therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
1
7
0
1
Order By: Relevance
“…The researchers showed that before the administration of biological treatment faecal markers can be an accurate measure of endoscopic and histological remission, but during the course of the disease they do not correlate as precisely with the endoscopic activity of the disease. The authors concluded that the biomarkers are useful in the long-term evaluation of biological treatment [21]. Our results are different to these observations, but consistent with data from Sipponen et al In our study, during the course of biological treatment the concentration of both calprotectin and lactoferrin decreased, which still correlated with the endoscopic and clinical activity of the disease.…”
Section: Discussionsupporting
confidence: 87%
“…The researchers showed that before the administration of biological treatment faecal markers can be an accurate measure of endoscopic and histological remission, but during the course of the disease they do not correlate as precisely with the endoscopic activity of the disease. The authors concluded that the biomarkers are useful in the long-term evaluation of biological treatment [21]. Our results are different to these observations, but consistent with data from Sipponen et al In our study, during the course of biological treatment the concentration of both calprotectin and lactoferrin decreased, which still correlated with the endoscopic and clinical activity of the disease.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, Kopylov et al (11) published a review article concerning the clinical utility of fecal biomarkers, including calprotectin, for the diagnosis and management of IBD. There is scarce information about the use of this test in Brazilian patients (18,32) . The aims of the present study were to prospectively investigate, in Brazilian adults with gastrointestinal complaints, the value of FC as a biomarker for the differential diagnosis between functional and organic disorders and to correlate the concentrations with the activity of IBD.…”
Section: Introductionmentioning
confidence: 99%
“…In another study of 115 CD patients, FC less than 300 μg/g was associated with a reduced risk of disease relapse . However, not all the data are in line with these observations, as reported in a prospective study measuring FC levels in patients undergoing infliximab induction . In these patients, FC measurement at 14 weeks could not predict CD clinical relapse at 1 year, suggesting a limit in the reliability of the marker over a long time.…”
Section: Discussionmentioning
confidence: 86%
“…Repeated measurement of FC indicates that a drop of pretreatment stool concentration is effective in predicting response to anti‐tumor necrosis factor‐α antibodies. Again, differing reduction values versus baseline were used for predicting favorable responses (Table ) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation